Relation between maternal body mass index and laboratory outcome in normal responder young patients undergoing intracytoplasmic sperm injection cycles - Bahgat, Nagwan Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: A lot of studies conducted evaluating the effect of maternal weight on the In Vito Fertilization (IVF) cycles outcome, the results of these studies were conflicting. Methods: We conducted retrospective cohort study on young normal responding patients attending the clinic for fertility treatment. Patients divided in to three group according to their body mass index (BMI). All patients had intra cytoplasmic sperm injection cycle with antagonist protocol. The IVF laboratory outcome was calculated and compared between the three groups. Results: The intracytoplasmic sperm injection cycles laboratory outcome was evaluated in the three groups of patients. No significant difference was found between the laboratory out come in the three group. Conclusions: We concluded that in absence of sever major factor for infertility, maternal BMI has no effect on the laboratory outcome of intra cytoplasmic sperm injection cycles.